KOMUNIKASI PEMASARAN TENUN CAGCAG SEBAGAI DAYA TARIK WISATA BUDAYA BERBASIS MASYARAKAT - Made Ika Kusuma Dewi (UHN IGB Sugriwa Denpasar, 2024)
Marketing communications for Cagcag weaving, Banjar Pesalakan, can develop into a community-based cultural tourism village. To keep cagcag weaving relevant in the global tourism market, an effective marketing communication strategy is needed. A local community-based approach is the key to creating an authentic and sustainable strategy. This article will discuss how marketing communications for cagcag weaving based on the local community of Pesalakan Banjar Pejeng Kangin Village can strengthen product identity and improve the economic welfare of local communities based on cultural tourism villages. Local community-based cagcag weaving marketing communication is an approach that utilizes the knowledge, skills and uniqueness of local communities to market cagcag weaving products. This approach aims to highlight the authenticity and cultural richness contained in cagcag woven products, especially the gegambir motif, while providing direct economic and tourism benefits to craftsmen and tourists. Keywords: Marketing Communications, Cagcag Weaving, Community Based Cultural Tourism